Medidas Explícitas e Implícitas de Atitudes Frente à Adoção e seus Correlatos Valorativos - Brasileiro, Tamíris da Costa (2014)
This dissertation aimed to know the extent of which human values and attitudes explain the intention during adoption. Thus, we chose three studies. Study 1 aimed to build two explicit measures of adoption, the Attitudes toward Adoption Scale (EAFA) and the Behavioral Intention of Adopting Scale (EICA). The participation consisted of 206 people from the general population of João Pessoa (in the State of Paraíba, Brazil), mostly female (60%) with a mean age of 32 years (SD = 7.61). The EAFA presented a structure containing three factors: availability to adopt (α = 0.89), risks associated with adoption (α = 0.78) and humanitarian aspects of adoption (α = 0.78), which together explain the 45% of the total variance. The EICA, in turn, showed contained only one factor, which explains 65.8% of the total variance under Cronbach's alpha of 0.86. Study 2 aimed to: a) confirm the factorial structures of the measurements of EAFA and EICA, and b) test the explanatory model of the intention to adopt, considering antecedent variables as values and explicit attitudes toward adoption. The sample consisted of 215 people from the general population, with an average age of 33 years (SD = 7.67), mostly female (51 %). They answered the measurements from study 1, in addition to the Basic Values Questionnaire (QVB), the scale of social desirability Marlowe - Crowne (EDSMC) and a sociodemographic questionnaire. The results allowed the confirmation of the factorial structure of EAFA and unifactorial structure of EICA, while pointing to the development of a theoretical model involving the supra-personal, interactive and experimental values in explaining attitudes towards adoption and these, in turn, predicting the intention to adopt. This model is suitable for empirical data [χ²/df = 2.40, GFI = 0.99, AGFI = 0.98, CFI = 1.00, RMR = 0.02 and RMSEA = 0.00 (0.06 - 0.00), PCLOSE (p = 0.92)]. Finally, Study 3 had the following objectives: c) construct a measurement tool to examine implicit attitudes toward adoption (IAT - Adoption), and d) develop an alternative model of intention to adopt to that proposed in the study, involving values and implicit attitudes towards adoption. 50 people participated from the general population, the majority was female (54.9%), single (56.9%) with mean age of 29.55 years (SD=6.49). Besides the implicit measurement, the same instruments were used in the study 2: QVB and EICA, beyond the demographic data. Overall, the results indicated that people have implicit attitudes favorable toward to adoption and that these are inversely correlated realizable values. The second theoretical model also was proven adequate [χ²/gl =1,33, GFI = 0,90, AGFI = 0,81, CFI = 0,97 e RMSEA = 0,08 (0,001-0,17); PCLOSE (p = 0,28)]. Therefore, the objectives of this thesis were met by developing explicit and implicit measurements, and testing two alternative models of the intention to adopt, and these presented satisfactory results using the variable values, and implicit and explicit attitudes toward adoption.